2010
DOI: 10.1007/s00009-010-0088-2
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Set Theory to ω + n-Totally p ω+n -Projective Primary Abelian Groups

Abstract: Several equivalent descriptions are given of the class of primary abelian groups whose separable subgroups are all direct sums of cyclic groups; such groups are called ω-totally Σ-cyclic. This establishes the converse of a theorem due to Megibben. For n < ω, this is generalized to a consideration of the class of primary abelian groups whose p ω+n -bounded subgroups are all p ω+n -projective. The question of whether there are such groups that are proper in the sense that they are neither p ω+n -projective nor ω… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…With this cardinality assumption, it is shown that V is uniquely realizable iff V (v n À 1) is countable; and in this case, every group G supported by V will be a dsc group. In particular, when n 1, Corollary 3.5 states that these groups agree with those described in ( [2], Theorem 2.6). Theorem 2.11 (i.e., the solution to the above question (2)) is a generalization of the classical``Existence Theorem for Principal p-Groups'' from [9]; in fact, for n 1, it reduces to precisely this result.…”
Section: Terminology and Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…With this cardinality assumption, it is shown that V is uniquely realizable iff V (v n À 1) is countable; and in this case, every group G supported by V will be a dsc group. In particular, when n 1, Corollary 3.5 states that these groups agree with those described in ( [2], Theorem 2.6). Theorem 2.11 (i.e., the solution to the above question (2)) is a generalization of the classical``Existence Theorem for Principal p-Groups'' from [9]; in fact, for n 1, it reduces to precisely this result.…”
Section: Terminology and Introductionsupporting
confidence: 69%
“…These groups were studied in [2], where, for example, it was shown that they are precisely the dsc groups G for which p v G is countable. Therefore, we have the following consequence of Theorem 3.4 for n 1.…”
Section: Case 2 Case 1 Does Not Applymentioning
confidence: 99%
See 1 more Smart Citation
“…Note that these groups G are classified in [4] up to an isomorphism using their Ulm invariants, together with the Ulm invariants of the totally projective groups E λ G, over all limit ordinals λ of uncountable cofinality. Next, since a direct sum of groups is (strongly) n-totally projective if and only if each of its terms has that property, and since the functor E λ G also respects direct sums (because λ has uncountable cofinality), we may assume that G is a λ-elementary A-group and that we possess a representing sequence as in (1). Notice that for any limit ordinal β < λ, we have a balanced-exact sequence implied via (1)…”
mentioning
confidence: 99%
“…The next example shows that the class of strongly n-totally projective groups is not contained in the class of ω + n-totally p ω+n -projective groups. Recall that in [1] a group G is said to be ω + n-totally p ω+n -projective group if each p ω+n -bounded subgroup is p ω+n -projective. Example 2.…”
mentioning
confidence: 99%